High-Order Questions Improve Students' Critical Thinking Skills In Elementary Schools - Widya Karmila Sari Achmad; Unga Utami (International Journal of Elementary Education, 2023)
Critical thinking is an essential and well-established skill for meeting workers' demands in the 21st century. In today's era, teaching and training students in critical thinking skills, even from elementary school, is essential. However, there are still many students who have low critical thinking skills. This study aims to analyze and describe the effect of the effectiveness of high-level questions in developing students' critical thinking skills in elementary schools. The research method used a one-group pretest and posttest experimental design, which was carried out in three elementary schools. The population of this study was three teachers and 102 students. Instruments in this quantitative research include questionnaires, observations, and interview guidelines. Data analysis techniques in this study are descriptive qualitative and quantitative analysis and inferential statistics. The study results showed a significant difference between the pretest and posttest scores of the students obtained from the results of studying the high-level questions. Second, high-level questions are practical for developing elementary school students critical thinking skills. It is concluded that high-order questions can improve critical thinking skills in elementary school students.